2019
DOI: 10.4012/dmj.2018-014
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the prediction models for surface roughness and micro hardness of denture teeth

Abstract: The paper aimed to compare the performance of artificial neural network (ANN) model with the results of in vitro experiments. For these experiments, maxillary molars of four different denture teeth were subjected to tea, coffee, cola, cherry juice, distilled water. Vickers microhardness and surface roughness values were measured. Subsequently, ANN model for the prediction of microhardness and surface roughness of different denture teeth were examined. A back-propagation ANN has been used to develop a model rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…A total of 13 studies were included to review the outcome of prosthodontic treatments using AI (Table 4). Among the 13 studies, 6 studies used AI in the prediction of dental prosthesis treatment outcomes [20][21][22][23][24][25]. One of the studies aimed to predict facial deformation after the insertion of complete dentures using a backpropagation (BP) neural network model.…”
Section: Prediction Of Prosthodontic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies were included to review the outcome of prosthodontic treatments using AI (Table 4). Among the 13 studies, 6 studies used AI in the prediction of dental prosthesis treatment outcomes [20][21][22][23][24][25]. One of the studies aimed to predict facial deformation after the insertion of complete dentures using a backpropagation (BP) neural network model.…”
Section: Prediction Of Prosthodontic Treatmentmentioning
confidence: 99%
“…Deniz S et al [22] used an ANN model to predict the surface roughness and microhardness of denture teeth and found that the experimental data were distributed along the ANN predicted line when the mean error of 7.6596 for microhardness and surface roughness were 4.0012.…”
Section: Prediction Of Prosthodontic Treatmentmentioning
confidence: 99%
“…Bahan gigi artifisial yang umum digunakan adalah resin akrilik dan porselen. 1,2 Gigi artifisial resin akrilik diperkenalkan sejak tahun 1937 dan masih digunakan sampai sekarang karena memiliki kelebihan, seperti mudah dimanipulasi, mudah dipoles, tidak mengikis gigi-gigi asli antagonis dan memiliki kekuatan ikatan yang baik dengan basis gigi tiruan. 3 Resin akrilik polimerisasi panas (RAPP) merupakan pilihan yang sering digunakan untuk pembuatan gigi tiruan karena estetis, tahan terhadap fraktur, harganya relatif murah, biokompatibel, mudah direparasi, mudah dimanipulasi dan mudah dipoles.…”
Section: Pendahuluanunclassified
“…BPNN acts as an interactive gradient model to reduce color mismatches between the predicted shade and the target shade. In backward propagation, when the color mismatch exceeds an acceptable limit, the shade determination process is back‐propagated by tuning the weights and biases, as a result, the process resumes till the color mismatch decreases to the acceptable limit 153 . For training a CCM system in dentistry by using BPNN, the color coordinates of a set of specimens can be used as inputs, while their equivalent porcelain powder recipes such as the weight of different types/layers of porcelain (body dentin and enamel) serve as outputs 154 .…”
Section: Tooth Shade Determinationmentioning
confidence: 99%